Heart rate monitoring in soccer: Interest and limits during competitive match play and training, practical application - Alexandre, D.; da Silva, C. D.; Hill-Haas, S.; Wong, D. P.; Natali, A. J.; de Lima, J. R. P.; Filho, M. G. B. B.; Marins, J. J. C. B.; Garcia, E. S.; Karim, C. (The Journal of Strength and Conditioning Research, 2012)
The identification of physiological loads imposed by soccer training or match play reveals essential information, which may help improve training and recovery strategies. Until today, the use of heart rate (HR) monitoring is not standardized in soccer. Thus, the aim of this review was to analyze, determine and compare the exercise intensity (EI) monitored by HR in professional, youth, and recreational soccer players during matches and training sessions using a meta-analysis. Heart rate is one of the most common physiological variables used to determine exercise internal training load. The mean EI recorded during competitive matches was described as 70-80% of VO2max or 80-90% of maximal heart rate (HRmax), independent of the playing level. With respect to HR training zones, approximately 65% of the total match duration is spent at intensity of 70-90% HRmax and rarely below 65% HRmax. However, although HRmax is mostly employed in the literature, monitoring EI should be expressed in relation to reserve heart rate, as it was described as a more reliable indicator of HR, allowing interindividual comparisons. The HR response according to the playing position indicates that midfielders are characterized by the highest EI, followed by forwards and fullbacks. Moreover, in the second half of the match, the EI is lower than that observed during the first half; this reduction could be correlated with the level of the player's physical conditioning. Consequently, coaches may favor the use of interval training or small-sided training games because these are shown to improve both aerobic capacity and the ability to repeat high-intensity actions. Small-sided games allow reaching similar HR responses to those found during interval training and match play but with greater heterogeneity values. Future investigations should include a larger sample of players with special reference to playing position and the expression of EI in percentage of the reserve heart rate, analyzing the possible intergender differences in HR response.